2008
DOI: 10.2495/etox080151
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the lead and cadmium contamination levels in the Lublin Region wetlands using mallards (Anas platyrhynchos) as a contamination vector

Abstract: Human activity emits vast amounts of heavy metals into the environment. Toxic elements that permeate through the biosphere are incorporated into the trophic chain where they are harmful to all living organisms. The aims of this research were: identification of risks and dangers to the environment in the Lublin Region associated with contamination of selected organs of the mallards by toxic elements; determination of concentration levels of selected heavy metals (Pb, Cd) in the organs and tissues of mallards (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Among all the tissues analysed in mallards, the highest average copper content was recorded in the liver. This is confirmed by previous research by 27 and by [35]. No statistical differences were shown in the average copper content in the liver between male and female mallards, which is in agreement with findings reported by [17] for birds of this species harvested in autumn in eastern Austria (37 mg•kg −1 WW).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among all the tissues analysed in mallards, the highest average copper content was recorded in the liver. This is confirmed by previous research by 27 and by [35]. No statistical differences were shown in the average copper content in the liver between male and female mallards, which is in agreement with findings reported by [17] for birds of this species harvested in autumn in eastern Austria (37 mg•kg −1 WW).…”
Section: Discussionsupporting
confidence: 93%
“…Lower average zinc concentrations in the liver of mallards than in the present study were obtained by [34] in birds harvested in Warmia-Masuria and in Silesia (24.288 mg•kg −1 DW and 26.112 mg•kg −1 DW, respectively), by [36] in mallards in Warmia-Masuria (21.49 mg•kg −1 WW), by [35] in birds in Tuligłowy (43.4 mg•kg −1 WW) and by [15] in the liver of mallards harvested in Kanibarazan in Iran (59.63 mg•kg −1 DW). Kalisi ńska et al [23], in mallards harvested in the Sło ńsk Reserve, showed a higher average level of this element in juveniles (48.44 mg•kg −1 WW) than in adults (42.66 mg•kg −1 WW).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The lowest lead concentration was found in the liver. Bojar et al (2008) mentioned liver as a tissue with the highest lead concentration. Mapping the lead distribution in individual organs and tissues is difficult in view of the inconsistency of the published results.…”
Section: Discussionmentioning
confidence: 99%